Mobile healthcare simulation units: a narrative review - Docherty, Charles; Rajani, Mehak; Shahpur, Numair; Khalid, Farah; Ukrani, Ronika Devi (Journal of the Pakistan Medical Association, 2023)
For healthcare professionals working and living in geographical isolation, there are few opportunities to maintain skills and knowledge, and to update theselves with recent advances in care compared to their city-dwelling peers. It is known that within a short period and limited practice, clinical skills erode. A mobile healthcare simulation unit provides high-quality, technologically-enhanced, convenient, and affordable training for healthcare professionals under expert supervision in any remote setting. The current narrative review was planned to summarise the outcomes and challenges related to developing and effectively utilising mobile healthcare simulation units as experienced globally. A literature search was performed on PubMed, Google Scholar and Cochrane databases for relevant articles published between 2000 and 2020, which resulted in 19 articles that were shortlisted and three major themes. ---Continue